História do número e: gênese e aplicações - Precioso, Juliana Conceição [UNESP]; Pedroso, Hermes Antonio [UNESP] (My University, 2013)
The aim of this paper is to present some fundamental aspects of the history of the number e, in particular those related to its origin, a little uncertain, and their unavoidable presence in the most diverse applications in various branches of science. We will highlight the importance of this number in compound interest problems, in the Napier’s logarithms, in the quadrature of the hyperbola, in the catenary problem and mostly in the lush Euler’s contribution to the subject.

O objetivo desse trabalho é apresentar alguns aspectos fundamentais da história do número e, em especial, os relacionados à sua origem, um pouco incerta, e sua presença inevitável nas mais diversas aplicações em vários ramos da ciência. Destacaremos a importância desse número em problemas sobre juros compostos, nos logaritmos de Napier, na quadratura da hipérbole, no problema da catenária e principalmente na exuberante contribuição de Euler ao assunto.
Keywords: O número e; Exponencial; Logaritmos